STRATEGI PENINGKATAN KINERJA GURU MELALUI POLA KOMUNIKASI INTERPERSONAL DAN KEPEMIMPINAN MANAJERIAL KEPALA MADRASAH YANG EFEKTIF - Pauji, Ade Ikbal (Manajerial | Journal Manajemen pendidikan islam, 2025)
Leadership is a key factor in determining the efficiency, effectiveness and improvement of school organizational performance, supported by the interpersonal communication skills of the madrasah principal in order to create harmony, understanding, and conformity of goals between leaders and their members, so as to increase the productivity and performance of good educational human resources. The purpose of this study was to reveal and analyze in depth the strategy for improving teacher performance at the Ci Doyang Private Middle School, Ciamis Regency through effective interpersonal communication patterns and managerial leadership of the madrasah principal. Data collection through in-depth interview methods, in-depth observation, and documentation studies. The results of the study interpret that in the managerial context of the madrasah principal at MTsS Ci Doyang as an effort to improve teacher performance, starting from the planning process, formulating the vision, mission, and goals of the madrasah, organizing various activities in improving teacher performance, fostering harmonious and togetherness traits and supportive cooperation, involving teachers in curriculum development towards teacher professionalism, improving the profession through workshops, providing learning motivation to continue studying, paying attention to teacher welfare and building a good work climate. Interpersonal communication that is established in the madrasah also becomes a factor that makes teachers feel appreciated and ultimately can be a motivation in improving performance. The results of the performance improvement are used as guidelines in performance evaluation, by giving awards and additional tasks as deputy head of the madrasah for teachers who have good performance.